Performance measurement for supply chain management and quality management integration: a systematic literature review - Machado, Marcio C. (2020)
The purpose of this paper is to present a conceptual framework for performance measurement (PM) for the integration of supply chain management (SCM) and quality management (QM). Design/methodology/approach: A systematic literature review on SCM and QM was conducted to develop key performance measures related to six areas of integration between QM and SCM: leadership; continuous improvement and innovation; sustainability performance; stakeholders; information system; and management and strategic planning. Findings: Supported by the literature concerning to supply chain quality management (SCQM) integration, a set of nine propositions about performance measures, that contribute to the integration of SCQM, were developed. Originality/value: This study contributes to QM practices within a supply chain environment from an integrated perspective. Additionally, the propositions have significant implications from both managerial and theoretical perspectives. This study also extends the concept of supply chain quality integration by focusing on key aspects of PM that may help to improve the overall performance of the supply chain.